YbfA Regulates the Sensitivity of Escherichia coli K12 to Plantaricin BM-1 via the BasS/BasR Two-Component Regulatory System - Chen, Xinyue; Liu, Yifei; Jin, Junhua; Liu, Hui; Hao, Yanling; Zhang, Hongxing; Xie, Yuanhong (Frontiers in Microbiology, 2021)
Plantaricin BM-1, a class IIa bacteriocin produced by Lactobacillus plantarum BM-1, shows obvious antibacterial activity against Escherichia coli. However, the mechanism underlying the action of class IIa bacteriocins against gram-negative bacteria remains to be explored. The purpose of this study was to investigate the role of YbfA, a DUF2517 domain-containing protein, in the response of Escherichia coli K12 to plantaricin BM-1. The growth curve experiment and MIC experiment showed that the sensitivity of E. coli to plantaricin BM-1 was decreased by a ybfA null mutation. Electron microscopy showed that the ybfA null mutation reduced the surface rupture and contraction caused by plantaricin BM-1, and mitigated the effect of plantaricin BM-1 on the morphology of the E. coli cell membrane. Proteomics analysis showed that 323 proteins were differentially expressed in E. coli lacking the ybfA gene (P < 0.05); 118 proteins were downregulated, and 205 proteins were upregulated. The metabolic pathways containing the upregulated proteins mainly included outer membrane proteins, integral components of the plasma membrane, regulation of cell motility, and regulation of locomotion. The metabolic pathways involving the downregulated proteins mainly included outer membrane protein glycine betaine transport, amino-acid betaine transport, and transmembrane signaling receptor activity. The results of the proteomics analysis showed that the protein expression of the BasS/BasR two-component system was significantly increased (P < 0.05). Moreover, the expression levels of downstream proteins regulated by this two-component system were also significantly increased, including DgkA, FliC, and MlaE, which are involved in cell membrane structure and function, and RT-qPCR also confirmed this result. The growth curve showed that the sensitivity of E. coli to plantaricin BM-1 was significantly increased due to deletion of the BasS/BasR two-component system. Thus, deletion of ybfA in E. coli can increase the expression of the BasS/BasR two-component system and positively regulate the structure and function of the cell membrane to reduce the sensitivity to plantaricin BM-1. This will help to explore the mechanism of action of class IIa bacteriocins against gram-negative bacteria.